Laporan Pelita III, 1979/1980-1983/1984 (Direktorat Jenderal Pengairan, Departemen Pekerjaan Umum, 1984)
Report on the implementation of the Third Five Year Development Plan for the Direktorat Rawa, 1979/1980-1983/1984.